S100A6 represses Calu‐6 lung cancer cells growth via inhibiting cell proliferation, migration, invasion and enhancing apoptosis. (18th May 2021) - Wang, Ting; Han, Suoli; Du, Ge
Abstract : S100 calcium binding protein A6 (S100A6) has been reported to involve in many kinds of cancers through regulating intracellular calcium homeostasis. Previous studies found that S100A6 increased in lung cancer patients' plasma and pleural effusion. This study focused on its function in Calu‐6 lung cancer cells. S100A6 gene was transferred into Calu‐6 lung cancer cell line by lentivirus vector, the empty vector transfected cells and the blank cells were set as control groups. MTT was evaluating cell proliferation. The transwell assay was reflecting cell migration and cell invasion. The flow cytometric analysis was detecting cell apoptosis and cell cycle of three groups (Calu‐6, Calu‐6/neo, Calu‐6/S100A6). Nude mouse tumorigenicity was then applied to evaluate S100A6's effect on cellular tumorigenicity. Compared with control groups, Calu‐6/S100A6 cells showed a weakening trend in the cell behaviours of proliferation, migration and invasiveness, while had an enhancement of cell apoptosis, with all P  < .05. The cell cycle of Calu‐6/S100A6 cells had a reduction of S phase and an increase of G1 phase ( P  < .05). In animal study, after 5 weeks of cell injection, the tumour bulk of Calu‐6/S100A6 group was smaller than controls, with P  < .05. Our results demonstrate S100A6 inhibits the growth of Calu‐6 lung cancer cells, as well as impairs Calu‐6's ability in tumorigenesis. At cellular level, S100A6 is supposed to act as a tumour suppressor gene in lung cancer.